2014
DOI: 10.1111/roiw.12118
|View full text |Cite
|
Sign up to set email alerts
|

Economic Insecurity: Editors' Introduction

Abstract: This supplement issue focusing on Economic Insecurity combines papers emphasizing measurement of trends and cross-national comparisons of economic insecurity with papers discussing its policy determinants and social implications. In general, economic insecurity is about the looming economic dangers that affect people's lives in many spheres, from the fear of losing one's job to the anxiety of not being able to make ends meet. As Stiglitz et al. (2009) have argued, measuring economic insecurity is fundamental t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moreover, labor market and fertility decisions may be affected by insecurity and may impact current and future physical and mental health (Smith et al , ; Barnes and Smith, ; Modena et al , ; Rohde et al , , ; Staudigel, ; Watson, ). Therefore, insecurity should be included in any analysis of well‐being, as current and future inequality could be affected by the dynamics of individual behavior (Boarini and Osberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, labor market and fertility decisions may be affected by insecurity and may impact current and future physical and mental health (Smith et al , ; Barnes and Smith, ; Modena et al , ; Rohde et al , , ; Staudigel, ; Watson, ). Therefore, insecurity should be included in any analysis of well‐being, as current and future inequality could be affected by the dynamics of individual behavior (Boarini and Osberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Hacker et al () have proposed an ‘Economic Security Index’, designed to ‘fill a gap in existing theoretical and empirical analyses’ for research and policy analysis, but also conclude that ‘Ultimately, no single measure can capture all aspects of economic security’, which Stiglitz et al. saw as ‘fundamental to understanding people's economic wellbeing and to giving economic policy a wider perspective than that provided by static measures of poverty and material deprivation' (Boarini and Osberg, , p S1).…”
Section: Measurement Challengesmentioning
confidence: 99%
“…The former group of measures have long been linked to the idea of intra or intergenerational transmission of opportunities, while the latter are more clearly identified in the literature as proxies for economic insecurity. Boarini and Osberg (2014) point out that "economic insecurity is about the looming economic dangers that affect people's lives in many spheres, from the fear of losing's one's job to the anxiety of not being able to make ends meet" (p. S1). In sum, insecurity reflects the individual uncertainty about future economic losses guided by either observing what is happening to others or by the actual occurrence of an adverse event within one's household (job losses, death of main breadwinner, salary cuts, etc.).…”
Section: Income Mobility and Economic Insecuritymentioning
confidence: 99%
“…Since Stiglitz, Sen, and Fitoussi (2009), it has become clear that measuring economic insecurity is a key issue to understand individual well-being. Most recently, Boarini and Osberg (2014) underline that approaching the idea of uncertainty about economic losses and the extent to which this impacts well-being are main aims for research, more so when economic shocks are severe, have a long duration and include relevant losses for a wide range of individuals in society. A large number of works have demonstrated that income instability and perceived insecurity have an impact on well-being (Hacker et al, 2014), and a consideration of the prevalence of losses is particularly relevant (Ja¨ntti, Kanbur, Nyyssola¨, & Pirttila, 2013).…”
Section: Introductionmentioning
confidence: 99%